'A Most Gruesome Sight': Colonial Warfare, Racial Thought, and the Question of 'Radicalization' during the First World War in German South‐West Africa (Namibia). Issue 346 (6th June 2016) - ROSENGARTEN, ANDREA
Abstract: This article examines an episode of German military violence against civilians during the First World War in Namibia (formerly German South‐West Africa). Placing the violence against the Rehoboth Baster community in April–May 1915 within a longer history of German and other European colonial violence on the African continent, I argue that the tactics employed by the German military in Rehoboth – namely, collective punishment, destruction of property, and the refusal to distinguish 'civilians' from fighters – were normal and practised forms of warfare for European armies facing African communities that challenged colonial powers. With this in mind, I question the geographical scope of the 'radicalization' concept – the debated idea of the First World War as a turning point in a world history of violence against civilians, when new tactics and ideologies of warfare ushered in an unprecedented breakdown of distinctions drawn by armies between enemy 'civilians' and 'combatants'. The Rehoboth case provides an opportunity to explore the relationship of racial thought to the management and execution of violence during the First World War, at the level of complex local colonial entanglements.